Professional involvement - Foss-Kelly, Louisa L.; Moorhead, Holly Hartwig (A Guide to Graduate Programs in Counseling: Second Edition, 2025)
Entering a counselor education program is just the first step in becoming a Professional Counselor, which includes developing a solid Professional Counselor identity and a plan for a fulfilling career. In this chapter, the authors provide a step-by-step plan for understanding key elements of becoming a Professional Counselor, beginning to work as a Professional Counselor, and contributing to the counseling profession. These activities include professional involvement, service, and scholarship as well as other meaningful pursuits for building one's successful career. The authors present a professional involvement pyramid to illustrate how Counselors can engage in professional identity development from graduate school throughout their careers. © Oxford University Press 2025. All rights reserved.
Keywords: Counseling; Counselor education; Professional Counselor; Professional Counselor identity; Professional development; Professional service; dept.csp